Why Severability? A New Theory of the Effect of Invalid Treaty Reservations - Ulf Linderfalk (Groningen Journal of International Law)
The 1969 Vienna Convention on the Law of Treaties does not establish the effect of an invalid reservation to a treaty. Still, it leaves this issue to the discretion of legal decision makers. These have developed two different approaches to the problem. According to the first approach, a State that makes an invalid reservation to a treaty does not become a party. According to a second approach, the invalid reservation is severed, and the reserving State is a party without benefitting from the reservation. The second approach –the severability solution, so-called– can be observed mainly in the practice of human rights courts and treaty monitoring bodies. None of them have produced any complete and convincing explanation as to why the severability solution should be preferred to the alternative. Neither have any of the human rights scholars written about the issue. This article fills this critical gap. It introduces a new theory of the effect of invalid treaty reservations. This theory provides an answer to the general question of why, in the application of human rights treaties, the severability solution should be adopted, whereas in the application of many other treaties, it should not.